2016
DOI: 10.14712/23362936.2016.19
|View full text |Cite
|
Sign up to set email alerts
|

Can Anxiety Tested in the Elevated Plus-maze Be Related to Nociception Sensitivity in Adult Male Rats?

Abstract: Methamphetamine (MA) is one of the most addictive psychostimulant drugs with a high potential for abuse. Our previous studies demonstrated that MA administered to pregnant rats increases pain sensitivity and anxiety in their adult offspring and makes them more sensitive to acute administration of the same drug in adulthood. Because individuals can differ considerably in terms of behaviour and physiology, such as rats that do not belong in some characteristics (e.g. anxiety) to average, can be described as low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…As indicated in the Introduction of this paper, the presence or absence of aversive/anxiogenic effects after acute administration of meth has produced contradictory and inconsistent results (e.g., Beirami et al, 2017; Etaee et al, 2017; Pometlová et al, 2016). An examination of the subjects’ retreat behavior suggests that, unlike that which we have previously observed in animals running for IV cocaine (e.g., Ettenberg and Geist, 1991; 1993; Guzman and Ettenberg, 2007; Knackstedt et al, 2002), rats running for meth did not exhibit signs of any significant aversive consequences of the drug administration.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As indicated in the Introduction of this paper, the presence or absence of aversive/anxiogenic effects after acute administration of meth has produced contradictory and inconsistent results (e.g., Beirami et al, 2017; Etaee et al, 2017; Pometlová et al, 2016). An examination of the subjects’ retreat behavior suggests that, unlike that which we have previously observed in animals running for IV cocaine (e.g., Ettenberg and Geist, 1991; 1993; Guzman and Ettenberg, 2007; Knackstedt et al, 2002), rats running for meth did not exhibit signs of any significant aversive consequences of the drug administration.…”
Section: Discussionmentioning
confidence: 95%
“…While animal research should be able to more clearly answer this question, attempts to measure the anxiogenic/aversive effects of acute meth have produced contradictory and inconclusive results. Some studies employing an elevated plus maze show meth to be anxiogenic in that treated animals increased their latency to enter or spend time in the open arms of the apparatus (e.g., Beirami et al, 2017; Miladi-Gorji et al, 2015; Pometlová et al, 2016), while other studies have reported the exact opposite result and have suggested that the acute administration of the drug is anxiolytic (e.g., Etaee et al, 2017). In other work, dose-dependent decreases in social interactions have been observed after meth administration and hence may be another indicator of an anxiogenic response in rats (Šlamberová et al, 2010).…”
Section: Introductionmentioning
confidence: 99%